Prodasineura yulan (Odonata: Zygoptera: Platycnemididae), a new species from Sarawak - Dow, Rory A.; Ngiam, Robin W.j. (Zootaxa, 2013)
Prodasineura yulan is described from a male from Maludam National Park, Betong Division, Sarawak, Malaysian Borneo. It is allied to Prodasineura interrupta.